Exchange rate shock on Malaysian prices of imports and exports: An empirical analysis - Duasa, Jarita (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2009)
This study examines the significant impact of exchange rate shock on prices of Malaysian imports and exports. In methodology, the study adopts vector error connection (VECM) model using monthly data on nominal exchange rates, money supply, prices of imports and prices of exports covering the period of M1:1999 to M12:2006. For further analysis, we adopt an innovation accounting by simulating variance decompositions (VDC) and impulse response functions (IRF). VDC and IRF serve as tools for evaluating the dynamic interactions and strength of causal relations among variables in the system. In fact, IRF is used to calculate the exchange rate pass-through on import prices and export prices. The findings indicate that, while the exchange rate shock is significantly affect the fluctuation of import prices, the degree of pass-through is incomplete.